Praphesara Prahlāda Pradhāna, jībanī o smārakī paryyāẏa - Nepāka, Bhāgīrathi (Bhāgīratha Prakāśana ; Paribeshaka Buks Iṇṭaranyāsanāl, 1984)
Life and works of Prahlāda Pradhāna, 1910-1982, Oriya and Sanskrit scholar.